Hydrometallurgical Method for AgCu Alloy Powder Synthesis and Its Application in Pd(II) Recovery Through Cementation - Tomasz Michałek; Konrad Wojtaszek; Stanisław Małecki; Marek Wojnicki (Metals)
This study investigates the synthesis, characterization, and potential applications of silver–copper (AgCu) alloy powders produced from co-precipitated carbonates. The Cu/Ag carbonate samples were analyzed using EDXRF, TGA-DSC, XRD, SEM, and electrical conductivity tests to examine their composition, thermal behavior, structure, and morphology. The results showed slight deviations from the theoretical Cu/Ag ratios in the carbonates, attributed to equilibrium effects during precipitation. Thermal analysis indicated that the reduction process of carbonates with hydrogen was completed at 300 °C, while alloy formation was confirmed by endothermic peaks around 780 °C. XRD and SEM analyses revealed that AgCu alloys formed a solid solution, with smaller crystallite sizes observed at higher Cu contents. Electrical conductivity tests demonstrated that while pure Ag and Cu powders exhibited conductivity increases with compaction, the AgCu alloy showed stable conductivity without a significant decrease. In Pd(II) cementation experiments, AgCu alloys demonstrated higher efficiency in Pd(II) recovery than pure Ag and Cu. These findings suggest that AgCu alloys, particularly with a balanced composition, may offer improved performance for metal recovery applications, providing a promising approach for industrial cementation processes.